CROSS-SECTIONAL ANALYSIS OF PAIN AND UNFAVORABLE OUTCOMES AFTER SIMPLE TOOTH EXTRACTION AT LIAQUAT UNIVERSITY HOSPITAL DENTAL OUT PATIENT DEPARTMENT - Junaid Ali; Naeem Mustafa; Muhammad Awais (Journal of University Medical & Dental College, 2016)
ABSTRACT:OBJECTIVE: To assess intensity of post-operative pain and unfavorable outcomes after simple tooth extraction.METHODOLOGY: This cross-sectional analysis was conducted upon a sample 130 patients selected via convenience sampling from December, 2014 to July, 2015. The selected sample of patients presented at the Liaquat University Hospital Dental Out Patient Department. Assessment of general and dental unfavorable post-operative effects experienced was done. Subsequently, telephone interviews were made during evenings for a 3 days post-op. Pain intensity was assessed on a numeric scale, and use of analgesic drugs and pain quality were recorded.RESULTS: The greatest possibility of appearance of an unfavorable outcomes, was on day 2 post-extraction i.e. 66.9%, followed by day 3 post-extraction (20.8%). Pain was a predominant complaint that was felt till the third day. It was highest on the day of extraction (6.33 on a numerical scale with the upper limit of ten). The intensity of pain linearly declined on day 2 to day 3 i.e. from a mean score of 3.68/10 to 1.2/10. The most notable unfavorable outcome was of swelling on both, 42.3% on day 2 and 11.5% on day 3 of post-extraction. Other outcomes included dry socket, intensiﬁed sensitivity, bleeding and temporary depressive symptoms such as general aches, loss of appetite, anxiety and negative insight.CONCLUSION: Patients experienced pain of varying intensity after simple uncomplicated tooth extraction maximally at the day of extraction. The unfavorable outcomes, namely swelling, bleeding and intensiﬁed sensitivity, were, however, maximally experienced on day 2 post-extraction. We recommend offering regular analgesic drugs during the ﬁrst 3 days after tooth extraction to minimize the pain felt and advise greater care during the procedure to avoid unfavorable outcomes.